Asessment of halal governance issues in Malaysia / Ahmad Naqiyuddin Bakar, Harlina Suzana Jaafar & Nornadia Matulidi - Bakar, Ahmad Naqiyuddin; Jaafar, Harlina Suzana; Matulidi, Nornadia (UiTM Cawangan Johor, 2019)
This paper aims to assess the nature of halal governance and the relevant issues revolving around it. The specific objectives are to provide an overview of halal certification process within the framework of value chain; and to highlight issues on the halal governance scheme. Qualitative approach was adopted utilizing semi-structured interviews to understand in detail the stakeholders’ perception and experiences about governance framework on halal certification. Findings revealed that the current issues are pertaining to Political and Institutional Governance for Halal Certification; Regulatory and Operational Efficiency for Halal Related Agencies; and, Functional Ambiguity of Halal-Related Agencies. The study contributes significantly in the body of knowledge in terms of understanding and developing halal governance ecosystem as it unveils the stakeholder’s perspective in area that has been predominantly confined within academic experts’ point of view only.